An Overview of Mucosa-Associated Protozoa: Challenges in Chemotherapy and Future Perspectives - Santos, Helena Lucia Carneiro; Rebello, Karina M. (Frontiers in Cellular and Infection Microbiology, 2022)
Parasitic infections caused by protozoans that infect the mucosal surfaces are widely neglected worldwide. Collectively, Entamoeba histolytica, Giardia lamblia, Cryptosporidium spp. and Trichomonas vaginalis infect more than a billion people in the world, being a public health problem mainly in developing countries. However, the exact incidence and prevalence data depend on the population examined. These parasites ultimately cause pathologies that culminate in liver abscesses, malabsorption syndrome, vaginitis, and urethritis, respectively. Despite this, the antimicrobial agents currently used to treat these diseases are limited and often associated with adverse side effects and refractory cases due to the development of resistant parasites. The paucity of drug treatments, absence of vaccines and increasing problems of drug resistance are major concerns for their control and eradication. Herein, potential candidates are reviewed with the overall aim of determining the knowledge gaps and suggest future perspectives for research. This review focuses on this public health problem and focuses on the progress of drug repositioning as a potential strategy for the treatment of mucosal parasites.